"Cutaneous-type" angiosarcoma arising in a mature cystic teratoma of the ovary. Issue 6 (26th May 2006) - den Bakker, M A; Ansink, A C; Ewing-Graham, P C
Abstract : Benign and malignant somatic tumours arising in mature cystic teratomas of the ovary are a rare but recognised phenomenon. Squamous cell carcinoma is the most common somatic malignancy arising in ovarian teratomas, although many other types of tumour have been described. An angiosarcoma with "cutaneous" type typical features arising in a dermoid cyst of the ovary is reported. Vascular tumours have only rarely been described as secondary somatic tumours in ovarian teratomas. The diagnostic features and complications of such tumours are described.